VII. Can the Digital Economy Boost the Trade Position of Countries Along the Belt and Road? - Ma, Jiaxing; Li, Guopeng (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
With the rapid development of digital technology, the digital economy has become an essential component of the global economy, injecting new impetus into international trade. With the "Digital Silk Road" development, the digital economy is becoming a new engine for economic and trade cooperation between China and countries along the "Belt and Road". This paper analyses the development level of the digital economy of countries along the Belt and Road through the TIMG index. It concludes that the overall development level of the digital economy of countries along the Belt and Road is still low and unbalanced, and the underlying reasons are analysed. Secondly, the impact of the digital economy on the trade status of countries along the route was analysed from three paths: trade costs, trade prices, and trade diversity. Finally, four relevant policy recommendations are proposed: digital technology, digital infrastructure, digital market, and digital governance.